ATTENUATION OF OXIDATIVE STRESS AND NEUROTOXICITY BY MK-801 (DIZOCILPINE) ON DIPENTYLPHTHALATE-INDUCED COGNITIVE DYSFUNCTION IN MICE - GAUTAM, SANDHYA RANI; JAIN, SEEMA; MEDIRATTA, PRAMOD KUMARI; BD, BANERJEE (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The aim of our research is to study the effect of dipentylphthalate (DPeP), a plasticizer on cognition and various oxidative stress markers in mice, and to explore the modulatory effects of MK-801. Methods: In the present study, experimental mice were orally treated with two doses (33 and 100 mg/kg) of DPeP for 28 days. Cognitive functions were assessed using spatial navigation task on Morris water maze (MWM) and step-down latency (SDL) in passive avoidance apparatus. Oxidative stress was assessed by examining the levels of malondialdehyde (MDA), glutathione (GSH), ferric-reducing antioxidant power (FRAP), and 8-hydroxy-deoxyguanosine (8-OH-dG) levels in whole brain of mice. Results: DPeP exposure led to a statistically significant increase of latency in spatial navigation task and significant decline in the SDL in passive avoidance apparatus when compared to the control groups. Oxidative stress markers showed a significant increase following DPeP administration as seen with rise in levels of MDA, 8-OH-dG, and a fall in GSH and FRAP levels. Conclusion: The present data suggest that DPeP could adversely affect learning and memory functions in mice by an oxidative stress-mediated neuronal damage and pre-administration of MK-801 has the potential to attenuate these effects.